2014
DOI: 10.1177/1545968314550368
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Based, Self-guided Home Therapy for Individuals With Severe Arm Impairment After Stroke

Abstract: Background Few therapeutic options exist for the millions of persons living with severe arm impairment after stroke to increase their dose of arm rehabilitation. This study compared self-guided, high-repetition home therapy with a mechanical device (the Resonating Arm Exerciser - RAE) to conventional therapy in patients with chronic stroke, and explored RAE use for patients with subacute stroke. Methods Sixteen participants with severe upper extremity impairment (mean Fugl-Meyer (FM) score = 21.4 ± 8.8 out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 72 publications
0
45
0
Order By: Relevance
“…This implies that the development of poststroke spasticity is related to neuronal plastic changes within the central nervous system after the initial injury [see reviews (47, 4547)]. Intensive therapy improves motor function, but has no effect on spasticity (48). A single dose of selective serotonin reuptake inhibitors (10 mg escitalopram) significantly increased spasticity (measured by reflex torque) without affecting muscle strength of spastic leg muscles after stroke (49).…”
Section: Poststroke Spasticity and Motor Recovery Are Mediated By Difmentioning
confidence: 99%
“…This implies that the development of poststroke spasticity is related to neuronal plastic changes within the central nervous system after the initial injury [see reviews (47, 4547)]. Intensive therapy improves motor function, but has no effect on spasticity (48). A single dose of selective serotonin reuptake inhibitors (10 mg escitalopram) significantly increased spasticity (measured by reflex torque) without affecting muscle strength of spastic leg muscles after stroke (49).…”
Section: Poststroke Spasticity and Motor Recovery Are Mediated By Difmentioning
confidence: 99%
“…Indeed, a study that used principal component decomposition to analyze the movement patterns associated with functional use of the hand found that >90 percent of the variance in hand kinematics could be explained by nine finger-thumb movement patterns similar to ones trained by the MusicGlove [50]. In this framework, practicing a key movement component that is used in a range of daily tasks may be more efficient at inducing functional recovery than practicing the individual tasks themselves [51][52][53], a hypothesis one could call "componentspecific training" in order to contrast it with the widely advocated approach of "task-specific training." A third possibility is that practice with the MusicGlove simply made the participants pay more attention to their hand, and thus they were more inclined to report an increased use of it in daily tasks.…”
Section: Increased Functional Use Of Hand After Musicglove Therapymentioning
confidence: 99%
“…In a previous pilot study with a stationary version of LARA, a device called RAE, we found that users with severe arm impairment (FM score = 21.4 points ± 8.8 SD out of 66) could move the levers and synchronize to the resonance of the device, created by springs attached to the levers, and that repeatedly moving the levers had a therapeutic benefit [6], [7]. We then made RAE into LARA by incorporating one-way bearings into the levers and found that people with severe arm impairment could also drive LARA overground [8], [9].…”
Section: Introductionmentioning
confidence: 99%